Programme of work for the short-term adaptive production oriented research on rice in the BRUMDEC Project - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
56 páginas.